Bedside ultrasound-guided genicular nerve block with corticosteroids and lignocaine for knee osteoarthritis improves pain and participation, and is safe in inpatient rehabilitation: a retrospective case series - Neo, Edmund J. R.; Lau, Trier T. N.; Thein, Khin Yamin; Tay, San San (Frontiers in Pain Research, 2025)
BackgroundKnee osteoarthritis (OA) is a common joint disorder that causes significant pain and disability. It can affect individuals undergoing inpatient rehabilitation, interfering with their participation in therapy and clinical improvement. While there are various treatment options available for this condition, such as the intra-articular corticosteroid injection, not all patients are suitable and symptoms may persist despite multimodal analgesia. The ultrasound-guided genicular nerve block (US GNB) induces analgesia by targeting the genicular nerves around the knee, and has emerged as a safe and effective intervention option. This is the first effort to document its application in the inpatient rehabilitation setting.MethodsThis was a retrospective case series. We reviewed the medical records of inpatients undergoing rehabilitation who underwent the US GNB for disabling knee OA between July 1, 2022, and August 31, 2023. The primary outcome was improvement in rehabilitation participation based on physiotherapist notes in the week following the procedure. Secondary outcomes were pain by visual analogue scale (VAS), ambulation distance, and the Western Ontario and McMaster Universities Arthritis Index (WOMAC), at pre-discharge, 1-month, and 3-month follow-up timepoints. Safety and adverse events were also retrospectively reviewed.ResultsNine patients were consented for recruitment in our study. Eight of them showed improvement in pain and/or participation in therapy. There were significant improvements in VAS scores (median change -3) and improvements in ambulation distance (median increase 8 m) between pre-injection and pre-discharge phases. However, these did not persist at the longer follow-up visits. There were no serious adverse events although 3 patients had recurrent pain at later dates, and required further procedures or surgical referral.ConclusionsThe US GNB is safe to perform for inpatients undergoing rehabilitation who experience pain from knee OA. We found that in nearly all patients, there was clinical improvement in their pain and participation in therapy. It can be an effective alternative when other analgesia options are less desirable or available, and can help to keep patients progressing on the road to recovery.